Web Development for HVAC Water Treatment Module - Shaffie, Muhammad Azhad; Yunus, Faizal Amin Nur; Rahim, Mohd Bekri; Razali, Mohd Nizamuddin; Abdul Rahman, Khairul Anuar (Research and Innovation in Technical and Vocational Education and Training, 2022)
Website is a platform used to obtain information whether in terms of learning, entertainment or purchase purpose. The importance of developing this website is to facilitate students who study the subject of HVAC Water Treatment. The purpose of this study is to design, develop and test the functionality of Digital Learning Content (DLC) base on teaching aids using a website platform. The design model of this study uses the ADDIE design model. The model has five phases which is analysis, design, development, implementation and evaluation phases. The development of this open system water treatment website uses the wix.com website as the software to produce this website. Wix.com was chosen because this online site has a variety of attractive template designs. The selection of the template is based on the suitability of the template for the development of this website. Study data were collected through three experts related to multimedia creative and the subject of HVAC Water Treatment. The results collected by the researcher through these experts showed a positive response to this site. Overall, the study developed an open system water treatment website that has functionality in terms of content and design of the website.